The Effectiveness of the Citizen Waste Bank (BASWARA) in Managing Household Waste in the Village Gulang, Mejobo, Kudus - Adiella Farizqiani; Rukhaini Fitri Rahmawati; Abdul Hamid Setyawan (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Background: Waste is a complex problem in Indonesia, with national production reaching 67.8 million tons in 2020 and 38.33% unmanaged. The negative impacts include environmental, health, and economic damage. The waste bank program increases public awareness about recycling and the economic value of waste, as well as encourages active participation. Although much research has been conducted, further exploration is still needed to understand the challenges of waste bank management. The purpose of this study is to analyze the effectiveness of the Citizen Waste Bank (BASWARA) management in increasing its impact on the environment, community, and local economy. The results of the analysis are expected to provide more comprehensive benefits for the environment and society in waste management. Method: This study uses a qualitative descriptive approach. Data was collected through observations, interviews with the Secretary of BUMDes, and waste management documentation. Data sources include primary data from interviews and observations and secondary data from documentation and annual reports of BUMDes. This method provides an understanding of waste sorting and management by the community. Result: The BASWARA program educates the people of Gulang Village about waste management, increasing awareness and active participation in sorting waste. The community gets a reward from the proceeds of the sale of garbage, which strengthens solidarity between residents. With good management, BASWARA contributes to environmental cleanliness and community welfare. Conclusion: Based on the analysis of the effectiveness of the BASWARA program in Gulang Village, it can be concluded that there is an increase in public awareness about waste management and providing economic incentives through the savings system. The active participation of residents reduces the volume of waste in the landfill and strengthens solidarity between residents. Cooperation between local governments and communities is essential for the program's sustainability. It is hoped that BASWARA will continue positively impacting the environment and society. This study explores the effectiveness of BASWARA in managing household waste in Gulang Village, Mejobo, Kudus. Against the background of complex waste problems in Indonesia, this study aims to analyze the impact of BASWARA on community solidarity and environmental welfare. Qualitative descriptive methods are used to collect data through observation and interviews. The results show that BASWARA has succeeded in increasing public awareness and active participation in waste management and providing economic incentives through the savings system. This program contributes to environmental cleanliness and strengthens solidarity between residents.